Status Resistensi Aedes aegypti dengan Metode Susceptibility di Kota Cimahi terhadap Cypermethrin - Firda Yanuar Pradani; Mara Ipa; Rina marina; Yuneu Yuliasih (ASPIRATOR - Journal of Vector-borne Disease Studies, 2011)
Abstracts: Vector control of dengue usually doing by using insecticides, whether by governmentor insecticides used in household. Using to much insecticides for long time can causedresistence of mosquito. This research aim to know resistance status of Aedes aegypti fromendemic rural in district Cimahi to cypermethrin (synthetic pyretroid). Resistance statusknowing by susceptibility methods (WHO standard) with using impregnated paper that containingcypermethrin 0.2% and 0.4%. Aedes aegypti spread by it for 15, 30, 45 and 60minutes. Number of mortality count by percentage death mosquito in each time and eachconcentration of cypermethrin. Data interpreted by WHO standard, which percentage ofdeath mosquito <80% is resistance, between 80-98% is tolerance and 99-100% is susceptible.Aedes aegypti from endemic rural in district Cimahi showed resistance of cypermethrin0.2% and 0.4%. This result showed that all mosquito still alive after 15 minutes spreadingby cypermethrin 0.2%, and only 6.7% mosquito death in cypermethrin 0.4%. After 30minutes, death mosquito counted 46.7% in cypermethrin 0.2% and 73.3% in 0.4%. 46.7%mosquito was death in 45 and 60 minutes spreading by cypermethrin 0.2% and 73.3% in0.4%. The result showed resistance ratio (RR50) of mosquito is 4.6. Aedes aegypti from endemicrural in district Cimahi showed a resistance to cypermethrin 0.2% and 0.4%.